HCI in Business, Government and Organizations : interacting with information systems : 4th International Conference, HCIBGO 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. Part 1 /: interacting with information systems : 4th International Conference, HCIBGO 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. Part 1. (2017) - Unknown
No abstract available